The big-five personality traits and quality of life in elderly Malaysian patients with diabetes mellitus: a cross-sectional study - Woon, Luke Sy-Cherng; PJ, Gosse; ES, Kaunismaa; RL, Mainland; R, Arun; Hatta Sidi (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
While diabetes mellitus is highly prevalent in the elderly population with significant impact on quality of life (QOL), we yet to know much about how personality traits affect QOL in this patient population. A cross-sectional study was conducted at Universiti Kebangsaan Malaysia Medical Centre with the aim to determine the relationship between personality traits and QOL among the elderly (aged ≥60 years) with diabetes mellitus. Sociodemographic and clinical information were obtained. QOL was assessed using the WHO Quality of Life-BREF (WHOQOL-BREF) questionnaire and personality traits were assessed using the Big Five Inventory (BFI) questionnaire. Depression and anxiety were measured with Beck Depression Inventory-II (BDI-II) and Generalized Anxiety Disorder 7-item (GAD-7) scale, respectively, and controlled for in all analyses. There were in total 170 study participants (median age=69.0 years; IQR: 65.0-73.0; 51.2% male). In stepwise linear regression models, higher conscientiousness scores (β=0.156; P=0.044) and lower neuroticism scores (β=-0.176; P=0.028) were associated with greater QOL in the physical health domain. Higher extraversion scores (β=0.209; P=0.001) and higher conscientiousness scores (β=0.248; P<0.001) were associated with greater QOL in the psychological health domain. Higher agreeableness scores (β=0.286; P<0.001) were associated with greater QOL in the social relationship domain. Finally, higher agreeableness scores (β=0.327; P<0.001) and lower neuroticism scores (β=-0.223; P=0.001) were associated with greater QOL in the environment domain. Personality traits were closely associated with all domains of QOL among elderly patients with diabetes mellitus. Premorbid personality may have important role in moderating the impact of diabetes mellitus on the lives of elderly patients.